Instruments for Assessing Patient Independence in Self-Care: A Scoping Review - Eriyani T; Shalahuddin I; Pebrianti S; Maulana I (Journal of Multidisciplinary Healthcare)
Theresia Eriyani,1 Iwan Shalahuddin,2 Sandra Pebrianti,3 Indra Maulana4 1Department of Basic Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, Jawa Barat, Indonesia; 2Department of Community of Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, Jawa Barat, Indonesia; 3Department of Medical-Surgical Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, Jawa Barat, Indonesia; 4Department of Psychiatric Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, Jawa Barat, IndonesiaCorrespondence: Theresia Eriyani, Faculty of Nursing, Universitas Padjadjaran Jl. Raya Ir. Soekarno, KM. 21, Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel +62 81394665577, Fax +622 287793411, Email theresia@unpad.ac.idAim: Measuring patients’ independence in caring for themselves is essential in nursing care, especially in the internal medicine room environment. Many patients with various conditions need help in self-care.Objective: To identify the right instrument to measure patients’ level of independence in performing self-care.Methods: The scoping review uses the PICO framework through PubMed, Science Direct, and Scopus databases.Results: Nine instruments/measuring tools can be used to measure the level of independence of patients in self-care, namely CDS, Barthel Index and MBI (Modified Barthel Index), SCHFI, ECOG, Self-care ability questionnaire, DCTAQ, and Revised Summary of Diabetes Self-Care.Conclusion: Some instruments have various assessment methods and scores but can provide helpful information for health practitioners to assess patient independence. The instrument has been tested for validity and reliability in multiple studies. No instrument is absolutely the best, as each instrument has its advantages according to its context and purpose of use.Keywords: measuring instruments, internal medicine, self-care, patient Independence level